In utero treatment of severe fetal anemia resulting from fetomaternal red blood cell incompatibility: a comparison of simple transfusion and exchange transfusion. (June 2016) - Guilbaud, Lucie; Garabedian, Charles; Cortey, Anne; Rakza, Thameur; Carbonne, Bruno; Houfflin-Debarge, Véronique
Abstract: Objective: To compare in utero exchange transfusions (IUET) and in utero simple transfusions (IUST) for the treatment of fetal anemia resulting from red blood cell fetomaternal incompatibility. Study design: Retrospective comparative study from January 2006 through December 2011. The two techniques were compared for effectiveness, complications, and neonatal outcomes. Results: 36 patients had 87 IUETs and 85 patients 241 IUSTs. Gestational age at the first transfusion was similar in both groups (IUET: 27 ± 3.8 weeks; IUST: 27 ± 4.7 weeks; NS) as was the initial fetal hemoglobin level (IUET: 6.4 ± 2.8 g/dL; IUST: 6.0 ± 2.5 g/dL; NS). No significant differences were noted for postprocedure complications or efficacy. The daily drop in hemoglobin level was similar in both groups (IUET: 0.41 ± 0.23 g/dL/day; IUST: 0.44 ± 0.17 g/dL/day; NS) as were the time intervals between two procedures. Gestational age at birth was earlier in the IUET group (34.4 ± 1.3 weeks vs 35.5 ± 1.8 weeks; p < 0.001), but the postnatal transfusions or exchange transfusions rates and the duration of intensive phototherapy did not differ. No significant differences were noted for the overall survival rates (IUET: 100%; IUST: 96.4%; p > 0.99). Conclusion: IUET does not appear to provide any benefits compared with IUST, neither to be associated with a higher complication rate. The choice of the technique depends on availability of packed blood cells with high hematocrit (70–80%).